An open, multicentre, randomized clinical study in patients with bullous pemphigoid comparing methylprednisolone and azathioprine with methylprednisolone and dapsone. (29th October 2017) - Sticherling, M.; Franke, A.; Aberer, E.; Gläser, R.; Hertl, M.; Pfeiffer, C.; Rzany, B.; Schneider, S.; Shimanovich, I.; Werfel, T.; Wilczek, A.; Zillikens, D.; et al.
Summary: Background: Current treatment of bullous pemphigoid (BP) is based on the long‐term use of topical and/or systemic corticosteroids, which are associated with a high rate of adverse events and increased mortality. Objectives: To study the corticosteroid‐sparing potential of azathioprine and dapsone. Methods: This was a prospective, multicentre, randomized, nonblinded clinical trial that compared the efficacy and safety of two parallel groups of patients with BP treated with oral methylprednisolone 0·5 mg kg −1 per day in combination with either azathioprine 1·5–2·5 mg kg −1 per day or dapsone 1·5 mg kg −1 per day. Nine German and Austrian departments of dermatology included 54 patients based on clinical lesions, positive direct immunofluorescence (IF) microscopy and detection of serum autoantibodies by indirect IF microscopy, immunoblotting or enzyme‐linked immunosorbent assay. The primary end point was the time until complete tapering of methylprednisolone, and the most important secondary end point was the cumulative corticosteroid dose. Results: In eight patients (five azathioprine, three dapsone), methylprednisolone could be discontinued after a median time of 251 days in the azathioprine group and 81 days in the dapsone group. The median cumulative corticosteroid dose was 2·65 g for azathioprine compared with 1·92 g for dapsone ( P = 0·06). The median numbers of days when corticosteroids were applied were 148 and 51, respectively ( P = 0·24). No significant difference in the number of adverse events was seen between the treatment arms. Four patients (8%) died within the observation period of 12 months. Conclusions: Due to the lower than intended number of patients, the results of the primary and secondary end points were not or only barely significant. Dapsone appeared to have a moderately higher corticosteroid‐sparing potential than azathioprine. The combination regimen of either drug with oral methylprednisolone is associated with a relatively low 1‐year mortality in this vulnerable patient population. Abstract : What's already known about this topic? Antibiotics like doxycycline and dapsone have been used clinically for the treatment of bullous pemphigoid for a long time, yet few data from clinically controlled studies are available. What does this study add? Following a recently published study on the noninferiority of doxycycline to oral corticosteroids in bullous pemphigoid, this study presents data on the safety and efficacy of dapsone compared with azathioprine. Dapsone appeared to have a higher corticosteroid‐sparing potential than azathioprine in the treatment of bullous pemphigoid. Linked Comment: Iwata. Br J Dermatol 2017; 177 :1155–1156 . Linked Comment: Żychowska. Br J Dermatol 2017; 177 :1156–1157 .